Sudan : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2020)
This Selected Issues paper on Sudan provides a first stock-taking of the scale, main transmission channels and potential costs of poor governance and corruption in Sudan and offers preliminary recommendations. A large body of literature and country analyses confirm that weak governance and corruption undermine economic growth, amplify income inequality and erode public trust in the institutions. According to international agencies and existing literature, Sudan has scored very poorly on compliance with rule of law best practices in the past. Effective implementation of preventive measures is important; particularly in relation to politically exposed persons. Transparency on beneficial ownership of legal persons and arrangements to prevent their misuse for laundering the proceeds of corruption are necessary. Transparency, accountability, and comprehensive communication should be the backbone of governance and anti-corruption reforms in each sector. Rationalizing tax exemptions and phasing out tax holidays would strengthen governance while boosting fiscal revenues.